SYARIAT ISLAM DI ACEH: SEBUAH MODEL KERUKUNAN DAN KEBEBASAN BERAGAMA - Marzuki Abubakar (Media Syari'ah, 2017)
Implementation of sharia laws in Acheh has been legalitimated by Indonesian constitution since 1999. However, its implementation has raised disagreements. This fact raised public concerns that it will trigger implosition, and/or the violation toward religious freedom especially for non-Muslims. The argument in this paper that people of non-Muslims living peacefully with Muslims, there is no imposition to perform Islamic law against non-Muslims, let alone imposition confidence. Islamic Law is only applicable to Muslims, non-Muslims is only expected to respect it.